Ta có: P = -28/5 < 0 => Phương trình luôn có 2 nghiệm phân biệt.
Áp dụng định lí viet ta có:
\(x_1x_2=-\frac{28}{3}\left(1\right);x_1+x_2=-\frac{m}{5}\left(2\right)\)
Theo đề bài: \(5x_1+2x_2=1\)
<=> \(5\left(x_1+x_2\right)-3x_2=1\)
<=> \(x_2=\frac{-m-1}{3}\)
=> \(x_1+\frac{-m-1}{3}=-\frac{m}{5}\)
<=> \(x_1=\frac{2m}{15}+\frac{1}{3}=\frac{2m+5}{15}\)
Thay vào (1) ta có: \(\frac{-m-1}{3}.\frac{2m+5}{15}=-\frac{28}{5}\)
<=> \(\left(m+1\right)\left(2m+5\right)=252\)
<=> \(\orbr{\begin{cases}m=-13\\m=\frac{19}{2}\end{cases}}\)
Vậy:...
Xét \(\Delta=m^2-45\cdot\left(-28\right)=m^2+560>0\forall m\)
Khi đó \(x_1=\frac{-m+\sqrt{m^2+560}}{10}\)
\(x_2=\frac{-m-\sqrt{m^2+560}}{10}\)
Khi đó \(5x_1+2x_2=\frac{5\left(-m+\sqrt{m^2+560}\right)+2\left(-m-\sqrt{m^2+560}\right)}{10}=\frac{-7m+3\sqrt{m^2+560}}{10}=1\)
\(\Rightarrow3\sqrt{m^2+560}=10+7m\)
\(\Rightarrow9\left(m^2+560\right)=49m^2+140m+100\)
\(\Rightarrow40m^2+140m-4940=0\)
\(\Rightarrow\orbr{\begin{cases}m=\frac{19}{2}\\m=-13\end{cases}}\)